Direct steerable pipe thrusting - Robison, Jon (ASCE manuals and reports on engineering practice ; no. 155, 2023)
"MOP 155 details how engineers and construction professionals can utilize the Direct Steerable Pipe Thrusting (DSPT) method to design and install pipelines"--